Pengaruh Motivasi dan Biaya Pendidikan terhadap Minat Mahasiswa Mengikuti Pendidikan Profesi Akuntansi (PPAk) (Studi Empiris pada Mahasiswa Akuntansi di Universitas Sebelas Maret Surakarta) - Widiyanti, Kania Nur Indah, Drs. Eko Sugiyanto , M.Si (2015)
The purpose of this study was to examine the career motivation,motivation quality, economic motivation, and the cost of education to the student's interest in participating in Professional Accounting Education (PPAk). This study is an empirical research with descriptive method using survey through questionnaires. These samples included 45 students S1 Accounting Department of Economics University of Sebelas Maret Surakarta from 2011 to 2012 with a sampling technique using a purposive sampling method. Analysis of the data with validity and reliability, multiple linear regression analysis previously performed classical assumption that normality test, heteroscedasticity and multicollinearity. As to test the hypothesis performed multiple linear regression, F test (test model),t test and testing the coefficient of determination (R²). The result showed that motivation affect the interest of the quality of accounting students to follow PPAk, evident from tcount amounted to 4.430> t table (2.023) (p = 0.000 <0.05), career motivation affect the interest of accounting students to follow PPAk, proved to be of value t count 2.909> t table (2.023) (p = 0.006 <0.05), the economic motivation affect the interest of accounting students to follow PPAk, evident from t count amounted to 2.581> t table (2.023) (p = 0.014 <0.05), and the cost of education affect the interest of students to follow PPAk, proved of value t count 3,896> t table (2.023) (p = 0.000 <0.05).